Manejo agronómico del cultivo de orégano (Origanum vulgare) y sus procesos agroindustriales - Franco Jiménez, Luis Alfredo (2021)
This document refers to the agronomic management of the oregano (Origanum vulgare) crop and its agro-industrial processes. There are no production statistics and scientific information on the organ in the country. Among the conclusions, it was determined that oregano is a secondary crop, so there is no technology generated in aspects related to fertilization, fertilization, irrigation, planting distances, sanitary management, etc; the importation of oregano could decrease, if the development of the crop is promoted and its productivity is improved; In our country there are approximately 500 species of medicinal plants, of which 288 are registered as the most used and 125 are widely marketed, including oregano and oregano is marketed internally and externally. The Ecuadorian population consumes oregano either in preparation of meals as well as as an alternative medicine to calm pain because this plant has healing properties that allows it to perform this function.